2001
DOI: 10.3406/arsci.2001.1000
|View full text |Cite
|
Sign up to set email alerts
|

Résultats préliminaires des études palynologiques et anthracologiques du site phénicien punique de Tharros (Sardaigne).

Abstract: This study is aimed at the reconstruction of the physic and anthropic environment in the phoenician- punic site of Tharros, located on the Western coast of Sardinia. Since its origin this site is characterized by the role of leadership in economy, craftsmanship and administration politics, that it will have in the punie eparchy of Sardinia. The samples traited for the palynological analysis were found to be quantitatively poor in pollen but mostly rich in pollen types (about 60). The reconstructed flora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Palynological studies in Sardinia are still rare, and applied mainly in archaeological contexts. Examples include interpretations of Early Neolithic (sixth millennium BC) coastal open-air sites (Lugliè et al 2012, Pittau et al 2012, palaeovegetation reconstructions from some Bronze Age sites (Buosi et al 2015, López et al 2005 and Phoenician sites (Acquaro et al 2001), a multidisciplinary approach (archaeological, palaeobotanical and geomorphological) to obtain information about the traditional use of seeds and fruits during Punic times and the vegetation of southern Sardinia and the ancient coastlines of the Santa Gilla Lagoon during Punic colonization (Buosi et al 2017), and the interpretation of burning rituals, with reconstruction of the vegetation of a cremation area in the Roman Imperial Age (third century AD; Buosi et al 2013). Changes in evergreen vegetation and the impact of human activity have been examined in central western (Di Rita & Melis 2013, Sabato et al 2015 and northern Sardinia (Beffa et al 2016).…”
mentioning
confidence: 99%
“…Palynological studies in Sardinia are still rare, and applied mainly in archaeological contexts. Examples include interpretations of Early Neolithic (sixth millennium BC) coastal open-air sites (Lugliè et al 2012, Pittau et al 2012, palaeovegetation reconstructions from some Bronze Age sites (Buosi et al 2015, López et al 2005 and Phoenician sites (Acquaro et al 2001), a multidisciplinary approach (archaeological, palaeobotanical and geomorphological) to obtain information about the traditional use of seeds and fruits during Punic times and the vegetation of southern Sardinia and the ancient coastlines of the Santa Gilla Lagoon during Punic colonization (Buosi et al 2017), and the interpretation of burning rituals, with reconstruction of the vegetation of a cremation area in the Roman Imperial Age (third century AD; Buosi et al 2013). Changes in evergreen vegetation and the impact of human activity have been examined in central western (Di Rita & Melis 2013, Sabato et al 2015 and northern Sardinia (Beffa et al 2016).…”
mentioning
confidence: 99%
“…In the case of Sardinia, several studies have already shown the importance of fruit growing in the local agriculture, including Vitis vinifera (grapevine) since the Bronze Age (Ucchesu et al 2015), Prunus domestica from the Phoenician and Punic periods (Ucchesu et al 2017) and a variety of other fruits, among which O. europaea has already been mentioned Sanna 2009, 2012;van Dommelen et al 2018;Sabato et al 2019). Moreover, the past presence of O. europaea in the area of Tharros and Mistras is already known thanks to results from studies of pollen, charcoal and wood remains, even if these techniques cannot separate wild and domesticated olives (Nisbet 1980;Lentini 1997;Acquaro et al 2001;Di Rita and Melis 2013;Mureddu et al 2020). Our results also agree with those from other parts of the western Mediterranean, which have shown the important roles of the eastern and western Phoenicians (Punic people) and the Greeks; this is particularly true for the development of gardening and the importance of fruit growing (Pérez-Jordà et al 2017.…”
Section: Discussionmentioning
confidence: 99%